How Do Underwater Cultural Heritage Sites Affect Coral Assemblages? - John H. R. Burns; Kailey H. Pascoe; Sofia B. Ferreira; Haunani Kane; Clifford Kapono; Toni L. Carrell; Andres Reyes; Atsuko Fukunaga (Remote Sensing, 2023)
Underwater cultural heritage sites (UCH), such as shipwrecks and sunken aircrafts, can provide physical structures to support coral recruitment and habitats for marine organisms. Conversely, these archaeological artifacts can also be detrimental to live coral and release pollutants into the environment. The military history of Guam has resulted in a high abundance of UCH sites on shallow coral reef habitats, and little is known about how these artifacts may affect the ecology of these natural systems. In this study, we used photogrammetry techniques to survey coral assemblages on both natural and artificial reef substrata. We statistically examined patterns in coral cover, diversity, richness, and 3D habitat complexity. Our results found significant differences in live coral cover and assemblage structure between natural and artificial reef substrata. The results from univariate modeling and multivariate analyses indicate that coral assemblage structure plays an important role in supporting 3D habitat complexity, and the archaeological artifacts themselves can be a significant source of habitat structure. There is still a lack of clarity as to the overall implications of archaeological artifacts on underwater habitats, and the approach described here can be applied elsewhere to better understand the ecological impacts of UCH sites on coral reefs.